Consumer perception, microbiological safety, and technological aspects of minimally processed vegetables in Brazil - Finger, Jéssica de Aragão Freire Ferreira (2022)
Minimally processed vegetables (MPV), also known as sanitized fresh vegetables, are ready-to-eat products that appeal to consumers looking for healthy meals. However, the presence of pathogens and the occurrence of foodborne illnesses associated with the consumption of MPV concern consumers, governments, and food companies. This doctoral study aimed to evaluate aspects related to the production, commercialization, consumption, and microbiological safety of MPV. The data obtained are described in five chapters. Chapter 1 addresses the main insights about MPV, highlighting the most important aspects about the market, processing steps and occurrence of microbial pathogens. Chapter 2 describes the processing steps in Brazilian processing plants that produce MPV, as well as the results of the microbiological analysis of fresh and MPV sold in the city of Sao Paulo/SP, Brazil. Chapter 3 shows data on the quality and microbiological safety of minimally processed parsley, focusing on the identification of bacteria belonging to the Enterobacteriaceae family using the proteomic method. In Chapter 4, the profile of Brazilian consumers of MPV was characterized, and their consumption habits and perceptions of microbiological risk were analyzed. Finally, in Chapter 5, the adequacy of the labeling of MPV sold in Brazil was verified. The results obtained contribute to a better understanding of the operational practices used in the production of MPV, as well as aspects related to the quality and microbiological safety of these products, compared to in natura vegetables. In addition, this study allowed the profile of MPV consumers, their consumption habits, and perceptions of microbiological risk to be characterized. These data are important as they complement the literature in this area and serve as subsidy for the development of microbiological risk assessment models associated with MPV consumption.